피지컬-스크린 인터랙션을 연결하는 사용자 경험(UX) 디자인 커리큘럼 제안 - 최정민; Jung-min Choi; 정의철; Eui-chul Jung (한국디자인포럼, 2016)
연구배경 컴퓨터 그래픽 기술의 발달로 전통적 제품 범주가 확장되고 있다. 제품의 피지컬 디자인 요소가 스크린 속으로 들어가면서, 피지컬 속성을 주로 다루는 제품디자이너도 스크린 정보를 다루는 UX 디자인 지식이 필요하게 되었다. 따라서, 본 연구는 디지털 제품의 피지컬 속성과 스크린 정보 속성을 함께 고려하는 제품 UX디자인 커리큘럼을 제안하는 것을 목적으로 한다. 연구방법 제품 변천 과정을 조사하여, 제품에서 인터랙션 기술이 도입되면서 제품 형태에서 피지컬과 함께 스크린 정보가 중요한 요소로 부각되고 있음을 고찰하였다. 이를 바탕으로, 제품 인터랙션 커리큘럼 개발 선행연구를 분석하고, 인터랙션 교육 내용을 기술 중심 지식과 사용자 중심 지식으로 구분하여 커리큘럼을 구성하였다. 그리고, 실제 수업 진행을 위한 인터랙션 프로토타이핑 방법으로, 피지컬 UX는 메이키메이키(Makey Makey), 스크린 UX는 프로세싱(Processing)을 선정하여 수업에 적용하였다. 연구결과 선행 커리큘럼이 기술 중심적으로 구성되어 있음을 분석하고, 최근 시나리오 기법을 활용한 사용자 중심적 시도가 있었음을 알 수 있었다. 이러한 분석을 바탕으로, 사용자 중심 UX 기획 프로세스와, 피지컬-스크린 인터랙션 디자인을 구현할 수 있는 새로운 커리큘럼을 구성하고 수업에 적용하여, 스크린과 사용자 행동을 매핑(Mapping)하는 다양한 결과물이 디자인되었다. 결론 제안한 커리큘럼은, 메이키메이키로 인해 프로그래밍 부담이 상대적으로 적어, 사용자 중심적 사고의 시간이 늘어나는 장점이 있으나, 주어진 기술의 틀을 벗어나기 힘든 단점이 여전히 존재하고 있다. 본 연구는 향후 제품 인터랙션 커리큘럼 및 프로토타이핑 기초 연구로 그 의의가 있다. Background The scope of product design has been extended along with the development of computer graphics technology. As the physical elements in products enter into the screen, UX design knowledge is required for product designers to deal with physical and screen properties together. Therefore, the purpose of this study is to propose UX design curriculum of bridging physical and screen interaction. Methods By studying the history of products, the fact was investigated that screen information has emerged as an important factor with the physical form of a product after interaction technology was introduced. The previous researches on the curriculum development were examined, and new curriculum was proposed by combining technology-based knowledge and user-centered knowledge for the content of the curriculum. After investigating various interaction prototyping methods used in previous interaction design courses, the Makey Makey and the Processing were selected for physical and screen UX respectively. Result Investigation on previous curriculums showed the focus has moved from technology to user-centered approaches. With this result, the curriculum was developed for learning UX planning process and incorporating screen interaction with product design. The curriculum was applied to interaction design courses and many outcomes were produced by mapping user behaviors on screen information. Conclusion The proposed curriculum is the less burden of programming relatively due to Makey Makey, and beneficial to spend more time to think users. However, it is still not easy to develop a product without considering the limitations of technology. This study has its significance as a foundation for further development of interactive product design curriculums and prototyping.